What they did in their previous life: The investment value of mutual fund managers' experience outside the financial sector - Gjergji Cici; Monika Gehde-Trapp; Marc-André Göricke; Alexander Kempf (University of Cologne, Centre for Financial Research (CFR), 2014)
We document that prior work experience of mutual fund managers outside of the asset management industry is valuable from an investment perspective in that it provides managers with a stock picking and industry timing advantage. Fund managers' stock picks from industries where they previously worked outperform stock picks from their non-experience industries by about three percent annually. Also, fund managers are better at timing the returns of their experience industries than those of other industries. Moreover, the investment value of managers' prior work experience is greater for industries comprised of stocks that are harder to value.
Keywords: G23; D83; J24; 330; Investor Learning; Investor Experience; Mutual funds